HUBUNGAN ANTARA KARAKTERISTIK RESPONDEN DAN TINGKAT STRES TERHADAP KEJADIAN HIPERTENSI - Febriansyah, Pratama; Fitri, Nurwijaya (JURNAL SMART ANKes, 2025)
Hypertension is a major public health problem in Indonesia, with stress being a significant contributing factor. Respondent characteristics such as age, gender, occupation, and education level have the potential to influence the relationship between stress and the incidence of hypertension, particularly in rural areas such as the Petaling Community Health Center in Bangka Regency. To analyze the relationship between respondent characteristics and stress levels on the incidence of hypertension in the working area of the Petaling Community Health Center, Bangka Regency in 2025. This study used a cross-sectional design conducted at the Petaling Community Health Center in Bangka Regency from October 2025 to November 2025. A total of 73 respondents were selected using purposive sampling. The inclusion criteria for respondents were aged 26-65 years and above, having hypertension, being a community member who sought treatment at the health center, and living in the working area of the Petaling Health Center, Bangka Regency. The instrument used was DASS. The analysis used in this study was the chi-square test and Fisher's exact test. Stress levels (p-value = 0.004) had a significant relationship with the incidence of hypertension. However, age (p-value = 0.331), gender (p-value = 0.246), education level (p-value = 0.570), and occupation (p-value = 0.926) were not significantly related to the incidence of hypertension. Conclusion: Of the five variables studied, there was one variable that was related, namely stress levels. The community has become more aware of the importance of health and conducts regular health checks to control high blood pressure. Keywords: Hypertension, Stress Level, Gender, Education, Occupation